2006
DOI: 10.1207/s15327930pje8101_6
|View full text |Cite
|
Sign up to set email alerts
|

Cyber and Home School Charter Schools: Adopting Policy to New Forms of Public Schooling

Abstract: Cyber and home school charter schools have silently become a prominent part of the charter school movement. These alternative school models differ from conventional schools by relying on parents and the Internet to deliver much of their curriculum and instruction while minimizing the use of personnel and physical facilities. This article examines how recent develop-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…The literature of cyber charter schools has focused much more strongly on policy and management than on academic outcomes, possibly as a result of early concerns about cyber charters competing with other schools, sometimes across school district boundaries (Huerta, Gonzalez, & d'Entremont, 2006;Thomas, 2002;Tucker, 2007). The small number of studies of achievement in cyber charter schools has made general comparisons between the cyber charters and other schooling formats difficult.…”
Section: Review Of Researchmentioning
confidence: 99%
“…The literature of cyber charter schools has focused much more strongly on policy and management than on academic outcomes, possibly as a result of early concerns about cyber charters competing with other schools, sometimes across school district boundaries (Huerta, Gonzalez, & d'Entremont, 2006;Thomas, 2002;Tucker, 2007). The small number of studies of achievement in cyber charter schools has made general comparisons between the cyber charters and other schooling formats difficult.…”
Section: Review Of Researchmentioning
confidence: 99%
“…Pilling (1999) indicates that the wide availability and use of the internet has revolutionized the potential for home school education. Additionally, Huerta et al (2006) report that the home charter school movement has connected to the internet, quietly challenging traditional in the class public school model. Apple (2007) notes that the new world of technology has opened entirely new venues for home school education.…”
Section: Home Education Movement Todaymentioning
confidence: 99%
“…Beyond these national surveys, Huerta and González (2004) estimated that over the five years preceding their study there had been approximately 60 cyber charter schools in 15 states serving over 16,000 students. Rotherham (2006) reported that there were 147 cyber charter schools in 18 states serving 65,354 students (or 4% of the total charter school population).…”
Section: Trends In Cyber Charter Schoolsmentioning
confidence: 99%